Loss of Mitochondrial Ndufs4 in Striatal Medium Spiny Neurons Mediates Progressive Motor Impairment in a Mouse Model of Leigh Syndrome - Chen, Byron; Hui, Jessica; Montgomery, Kelsey S.; Gella, Alejandro; Bolea, Irene; Sanz, Elisenda; Palmiter, Richard D.; Quintana, Albert (Frontiers in Molecular Neuroscience, 2017)
Inability of mitochondria to generate energy leads to severe and often fatal myoencephalopathies. Among these, Leigh syndrome (LS) is one of the most common childhood mitochondrial diseases; it is characterized by hypotonia, failure to thrive, respiratory insufficiency and progressive mental and motor dysfunction, leading to early death. Basal ganglia nuclei, including the striatum, are affected in LS patients. However, neither the identity of the affected cell types in the striatum nor their contribution to the disease has been established. Here, we used a mouse model of LS lacking Ndufs4, a mitochondrial complex I subunit, to confirm that loss of complex I, but not complex II, alters respiration in the striatum. To assess the role of striatal dysfunction in the pathology, we selectively inactivated Ndufs4 in the striatal medium spiny neurons (MSNs), which account for over 95% of striatal neurons. Our results show that lack of Ndufs4 in MSNs causes a non-fatal progressive motor impairment without affecting the cognitive function of mice. Furthermore, no inflammatory responses or neuronal loss were observed up to 6 months of age. Hence, complex I deficiency in MSNs contributes to the motor deficits observed in LS, but not to the neural degeneration, suggesting that other neuronal populations drive the plethora of clinical signs in LS.